2016
DOI: 10.1080/10916466.2016.1154869
|View full text |Cite
|
Sign up to set email alerts
|

Using biosurfactant producing bacteria isolated from an Iranian oil field for application in microbial enhanced oil recovery

Abstract: Microbial enhanced oil recovery (MEOR) is a useful technique to improve oil recovery from depleted oil reservoirs beyond primary and secondary recovery operations using bacteria and their metabolites. In the present study, the biosurfactant production potential of Bacillus licheniformis microorganisms that were isolated from oil samples of Zilaei reservoir in the southwest of Iran was explored under extreme conditions. Growth media with different temperatures of 40, 50, 60, and 70°C; salinities of 1, 3, 5, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…This organism was injected in sandstone core samples and allowed to grow and excrete biosurfactants for 7 days. The amount of oil recovered in this stage was almost 14% of OOIP (Daryasafar et al, 2016). Though these studies are limited, the potential of this direct injection approach is promising, but requires more testing.…”
Section: Injection Of Laboratory-cultivated Biosurfactant-producing Mmentioning
confidence: 97%
See 3 more Smart Citations
“…This organism was injected in sandstone core samples and allowed to grow and excrete biosurfactants for 7 days. The amount of oil recovered in this stage was almost 14% of OOIP (Daryasafar et al, 2016). Though these studies are limited, the potential of this direct injection approach is promising, but requires more testing.…”
Section: Injection Of Laboratory-cultivated Biosurfactant-producing Mmentioning
confidence: 97%
“…When poor oil recovery from oil wells is due to low permeability of the rock formation, or to the high viscosity of the crude oil, the ability of biosurfactants to reduce IFT between the flowing aqueous phase and the residual oil saturation can potentially improve the process efficiency and recover more oil (Banat et al, 2000). During the shut-in period, effecting an IFT reduction can significantly influence recovery of the oil during the initial stage, while later in the recovery process, both the produced biosurfactants and microorganisms -noting that microbial cells themselves can express IFT-reducing properties -can attach to the rock surface and alter its wettability (Daryasafar et al, 2016).…”
Section: Reduction Of Interfacial Tension (Ift) Using Biosurfactantsmentioning
confidence: 99%
See 2 more Smart Citations
“…It affects adsorbed oil on reservoir rock by changing the interfacial tension between oil and water. Several studies have been shown that oil recovery is improved by this mechanism [21][22][23][24][25][26][27][28][29][30][31][32][33].…”
Section: Wettability Alterationmentioning
confidence: 99%